Penempatan semula setinggan negeri Perak kawasan kajian : Rancangan Perkampungan Tersusun Seri Murni, Seri Keramat dan Tok Chendang, Mukim Ulu Kinta, Daerah Kinta - Sipun, Halizah (2010)
Squatter’s resettlement always become a big concern and main predicament in any redevelopment programme. These issues at all the time become obstacle in implementing development planning as Government has to reconcile all the issues relating to the squatters. In the State of Perak, the state government announced the target of achieving Zero Squatters in 2010. Government has form four committees in state and district level to plan, implement and monitor the squatter’s eradication programmes. The committees formation supported by four other means to achieve the target of Zero Squatters in 2010. The State Government of Perak has fixed the decision that the squatters problem considered solved once the land title registered and the owner been given the Temporarily Occupancy Licence. According to that, the study focused on the mechanisms used by the State Government to eradicate the squatters and to get their perception on government move to relocate them. The findings of the study show that the squatters people are willing to be relocate but they hope that State Government taken into consideration their needs. At the same time, Perak State Government using the apologetics way by putting into the priority the squatter’s wellbeing in implementing the resettlement programme.